POSTMODERNIST ANALYSIS OF THE PILLOWMAN - DEVRİM, Nehir (Zenodo, 2022)
Postmodernism is among the most discussed subjects in contemporary world. Despite the criticism, postmodernism has been thriving in many different subject areas after modernism’s failure in keeping its promise for a “better life”. This paper mainly aims to examine and discuss devices and techniques used in the 2003 play The Pillowman by Martin McDonagh in the light of postmodernism. This study will examine postmodernist features and devices such as intertextuality, narratives/grand-narratives, black humor, metafiction, hyperreality, self-reflexivity, irony, paranoia, fragmentation, maximalism, allegory and late capitalism within the play, aiming to bring a better understanding to both postmodernism and The Pillowman.
Keywords: in-yer-face theatre; Martin McDonagh; The Pillowman; postmodernism